PRACTICAL USE OF MODERN INVESTIGATION AND MONITORING METHODS IN POLISH LANDSLIDE REMEDIATION PROJECTS - Zbigniew Bednarczyk (Acta Polytechnica CTU Proceedings)
This paper discusses exemplary landslide investigations in natural Carpathian and man-made opencast mine slopes. Research methods included mapping, core drilling, laboratory testing, GPR scanning, on-line inclinometer, piezometer, and pore pressure monitoring and also numerical modelling. Landslide triggers were complex and diverse. On flysch slopes movements were activated by heavy rainfalls and in opencast mines, by exploiting the parameters of clayey soils. Precise prediction of landslide activation is impossible. Identification of landslide triggers for mitigation measures requires a multiple analysis of integrated external and internal variables.